Systematic Review of the Literature on Augmented-Reality Mobile Applications for School Education - Alberto Cahuana-Cadagán; Rodrigo Barreto-Castillo; Javier GAMBOA-CRUZADO; Hilda JÁUREGUI-ROMERO; Elizabeth CANALES-AYBAR; Mauro CRUZADO-VIERA; Alfonso TESÉN-ARROYO (Communications of International Proceedings, 2021)
The school education that is currently being developed is still based on a traditional learning model where the students do not make use of their creativity and tend to be passive subjects with little initiative, insecurity, and scarce interest in the learning process. This generates a learning based on a rigid, hardly dynamic, system. This article provides a complete review of different studies reported in the last 5 years that focused on school education using augmented reality. After an exhaustive search and filtering of articles, we selected 101 papers that focused on augmented-reality mobile applications in school education. The results of this systematic review allow us to have a vision of the potential of implementing augmented reality in school education in contrast to traditional teaching in various school subjects. We also provide an overview of the most used tools for the development of these applications. Finally, this study has allowed us to know the state of the art on the impact of mobile applications with augmented reality in school education based on the aforementioned review of articles published between 2015 and 2020.
Keywords: Systematic Literature Review; Augmented Reality; School Education; Mobile Applications; Teaching-Learning.